2009
DOI: 10.1677/jme-09-0095
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise loss of motilin and its specific receptor genes in rodents

Abstract: Specific interactions among biomolecules drive virtually all cellular functions and underlie phenotypic complexity and diversity. Biomolecules are not isolated particles, but are elements of integrated interaction networks, and play their roles through specific interactions. Simultaneous emergence or loss of multiple interacting partners is unlikely. If one of the interacting partners is lost, then what are the evolutionary consequences for the retained partner? Taking advantages of the availability of the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 30 publications
3
93
1
Order By: Relevance
“…Suncus stomachs were used for in vitro contraction experiments. Motilin is a peptide hormone that stimulates gastric contraction similarly to ghrelin, and it is not expressed in rodents such as mice and rats (52). Suncus murinus is a small mammal that expresses both motilin and ghrelin; thus, it can be used to study motilin-ghrelin family peptides (53).…”
Section: Resultsmentioning
confidence: 99%
“…Suncus stomachs were used for in vitro contraction experiments. Motilin is a peptide hormone that stimulates gastric contraction similarly to ghrelin, and it is not expressed in rodents such as mice and rats (52). Suncus murinus is a small mammal that expresses both motilin and ghrelin; thus, it can be used to study motilin-ghrelin family peptides (53).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, although it is still debated whether or not native GPR38 (motilin receptor) is expressed (15), central administrations of motilin and GM-109 (a motilin antagonist) were respectively shown to increase food intake and reduce anxiety (1,27). These and numerous other studies suggest that rodents are a useful model for motilin studies.…”
Section: Discussionmentioning
confidence: 99%
“…In human and animal (mainly rabbit and pig) models, GPR38 is expressed in the smooth muscle layer and the mucosa of the GI tract, the amygdala, the mesenteric neurons, and the hippocampus (21,40,41,49). In mice, it is presently debated whether or not the motilin receptor is truly expressed or is simply present as a pseudogene (15). Meanwhile, direct motilin injection or administration of GPR38 agonists and antagonists were shown to induce biological effects in rodents (2,36).…”
mentioning
confidence: 99%
“…Studies in rodents have shown that motilin administration can stimulate food intake (27,28). However, these results need to be interpreted with caution because other studies reported that motilin and the motilin receptor exist only as pseudogenes in rodents and are therefore not functional (29,30) Although the expression of motilin and the motilin receptor has been demonstrated in humans, studies on the effect of motilin on food intake in humans are lacking (13,31,32). In this study, we have shown that the effect of the motilin receptor agonist erythromycin on hunger is regulated via a cholinergic pathway because pretreatment with atropine abolished both the increase in hunger and the induction of phase III contractions.…”
Section: Figurementioning
confidence: 95%